2014
DOI: 10.1007/s11920-014-0519-z
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing and Psychiatric Disorders

Abstract: Sleep-disordered breathing, the commonest form of which is obstructive sleep apnoea (OSA) is increasingly recognised as a treatable cause of morbidity. It shares many risk factors with psychiatric disorders including behaviours such as smoking and physical comorbidity. Many symptoms of the two overlap, leaving OSA often undetected and undertreated. In the few studies that assess the two, OSA is commonly comorbid with depression (17-45%) and schizophrenia (up to 55%) and possibly bipolar. There is some limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 89 publications
0
23
0
2
Order By: Relevance
“…Insomnia and poor sleep quality has been linked to worse symptom severity and poor outcome in bipolar disorder (Wu and Bunney 1990, Colombo, Benedetti et al 1999, Bauer, Grof et al 2006, Perlman, Johnson et al 2006, Gruber, Harvey et al 2009, Gruber, Miklowitz et al 2011). Also, sleep-disordered breathing, primary insomnia and sleep phase disorders are often comorbid with bipolar disorder, begging the question of these pathologies being related to the underlying mood pathology (Kripke, Mullaney et al 1978, Wehr 1992, Harvey 2008, Soehner, Kaplan et al 2013, Naqvi, Wang et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Insomnia and poor sleep quality has been linked to worse symptom severity and poor outcome in bipolar disorder (Wu and Bunney 1990, Colombo, Benedetti et al 1999, Bauer, Grof et al 2006, Perlman, Johnson et al 2006, Gruber, Harvey et al 2009, Gruber, Miklowitz et al 2011). Also, sleep-disordered breathing, primary insomnia and sleep phase disorders are often comorbid with bipolar disorder, begging the question of these pathologies being related to the underlying mood pathology (Kripke, Mullaney et al 1978, Wehr 1992, Harvey 2008, Soehner, Kaplan et al 2013, Naqvi, Wang et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Higher depression is caused by daytime sleepiness, and the resulting fatigue and, vice‐versa, higher level of depressive symptoms can be understood as a risk factor in the development of EDS (Aloia et al, ; Antic et al, ). We found that 3 months of CPAP treatment of patients with OSA had a beneficial effect on the level of depressive and trait anxiety symptoms (Acker et al, ; BaHammam et al, ; Ejaz et al, ; Fidan et al, ; Naqvi et al, ; Ryan, Bayley, Green, Murray, & Bradley, ; Sanchez, Buela‐Casal, Bermudez, & Casas‐Maldonado, ). These effects were highly significant, because they survived Bonferroni correction.…”
Section: Discussionmentioning
confidence: 98%
“…Complete (apneas) or partial (hypopneas) obstructive events in OSA, resulting in intermittent hypoxaemia, disturb sleep, causing its fragmentation, which is then a condition leading to excessive daytime sleepiness (EDS) (Barbe et al, ; Bucks, Olaithe, & Eastwood, ; Slater & Steier, ; Zhou et al, ). The resulting reduced blood oxygen saturation and disturbed sleep architecture may determine neurocognitive dysfunction and mood disorders in patients with OSA (Bucks et al, ; Jackson, Howard, & Barnes, ; Lal et al, ; Naqvi, Wang, Glozier, & Grunstein, ; Zhou et al, ). Cognitive impairment with OSA is mainly characterized by a lower level of attention and vigilance, reduced learning and memory, and decreased executive performance (Jackson et al, ; Lal et al, ; Rouleau, Decary, Chicoine, & Montplaisir, ; Tulek et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up objective testing with in-laboratory polysomnography or home portable monitors may be warranted [50]. A high prevalence of sleep disordered breathing has been found among individuals with schizophrenia [51]; one study found that nearly half of people with schizophrenia who were referred to a sleep clinic while hospitalized on a psychiatric inpatient unit met criteria for OSA, defined as a respiratory disturbance index greater than 10 events per hour [52]. Compared to others from the inpatient unit who were referred to the sleep clinic, those with schizophrenia were significantly heavier and experienced higher rates of OSA; when present, OSA was in the severe range.…”
Section: Diagnosismentioning
confidence: 99%